The Existence of Female Dancers in the Development of Dolalak Art in Purworejo Central Java - Yulianti, Eni; Martiara, Rina; Lies Apriani, Winarsi (Jurnal Seni Tari, 2024)
Dolalak is a traditional dance that appeared and developed in Purworejo, Central Java. In the beginning of its appearance, this dance was performed by men. In the 1970s, the government intervened to promote the art as a regional asset. Soepanto Regent's initiative, which encouraged women to be able to dance Dolalak, received positive support from society. Dolalak is considered more attractive and has greater marketing potential by women. So, 1970 became the first stage of Dolalak's rapid development. At the same time with the presence of Dolalak Putri or Female Dancer of Dolalak, the male Dolalak dancer began to be less desirable and even forgotten. This research will analyze the existence of female dancers in Dolalak art with a modern Sociology approach using the theory of Phenomenology from Peter L. Berger.  This analysis is based on Berger's formulation of the interrelationship between objective social reality and subjective knowledge based on reality and social interaction in daily life. The existence of Ambarwati's case as a Dolalak preservationist figure with high popularity with her predicate as "Ratu Dolalak". Ambarwati's popularity as a Dolalak dancer is not only utilized on her body but also accompanied by experience and knowledge from art education that makes her role in the performance more interesting. This makes Ambarwati's presence idolized.